2023
DOI: 10.1192/bjo.2023.22
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between blood–brain barrier dysfunction and neurocognitive impairments in first-episode psychosis: findings from a retrospective chart analysis

Abstract: Background Even before the onset of psychotic symptoms, individuals with schizophrenia display cognitive impairments. Simultaneously, increasing amounts of individuals exhibit dysfunction of the blood–brain barrier (BBB). However, the impact of BBB dysfunction on neurocognitive impairment in people with first-episode psychosis has not yet been investigated. Aims To advance understanding of said relationship, we considered one of the largest first-episode psychosis cohorts with cerebrospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The gut microbiota affects the permeability of the BBB even before birth, with germ-free (GF) mice showing increased permeability due to reduced expression of occludin and claudin-5. This interaction suggests that the gut microbiota plays a critical role in maintaining the integrity of the BBB and, by extension, in neurological health [67,68].…”
Section: Impact Of Blood-brain Barrier Dysfunction and Microbiota On ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota affects the permeability of the BBB even before birth, with germ-free (GF) mice showing increased permeability due to reduced expression of occludin and claudin-5. This interaction suggests that the gut microbiota plays a critical role in maintaining the integrity of the BBB and, by extension, in neurological health [67,68].…”
Section: Impact Of Blood-brain Barrier Dysfunction and Microbiota On ...mentioning
confidence: 99%
“…Research on schizophrenia has also identified various risk factors, from prenatal life to adolescence, that interact with the gut microbiota, suggesting a significant role of the latter in the manifestation of psychotic disorders. From maternal infections and prenatal stress to smoking and urban environment in adolescence, these factors can influence the composition of the gut microbiota, affecting the integrity of the BBB and contributing to the development of psychotic disorders [50,68].…”
Section: Impact Of Blood-brain Barrier Dysfunction and Microbiota On ...mentioning
confidence: 99%